Analysis of Knowledge and Skills among Special Education Teachers in Inclusive Schools in Indonesia - Cahyani, Leni Ambar; Subagya, Subagya (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This research examined the knowledge and skills of special education teachers within the context of inclusive education in Indonesia. Employing a quantitative survey approach, the study aimed to determine whether a statistically significant disparity existed between these two variables. The data collection technique utilized included knowledge tests and performance assessments, involving 637 participants from 26 districts/cities. The data analysis technique employed was the t-test using SPSS. The research findings indicated that the mean knowledge score (51.85) was lower than the mean skill score (73.90). The t-test result showed a value of -29.87 with p-value <0.05, indicating a significant difference between the knowledge and skill scores. Several factors contributed to the higher skill scores, including limited access to specialized training and professional development, curriculum structures prioritizing skill-based coursework, and the unique demands of inclusive education settings.